2018
DOI: 10.1523/jneurosci.1669-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Latent Factors and Dynamics in Motor Cortex and Their Application to Brain–Machine Interfaces

Abstract: In the 1960s, Evarts first recorded the activity of single neurons in motor cortex of behaving monkeys (Evarts, 1968). In the 50 years since, great effort has been devoted to understanding how single neuron activity relates to movement. Yet these single neurons exist within a vast network, the nature of which has been largely inaccessible. With advances in recording technologies, algorithms, and computational power, the ability to study these networks is increasing exponentially. Recent experimental results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 113 publications
3
38
0
Order By: Relevance
“…The patterns of the attention weights suggested that the previous neural activity is essential for neural decoding during the preparatory period and execution of the movement, whereas the most recent neural activity is essential during the release phase. This finding is consistent with observations made in [ 5 , 36 , 37 , 38 ], where preparatory neural activity served as an initial condition for subsequent activity patterns. For the instructed delayed reach-to-grasp task, all findings from the three RNN-based neural decoders suggest that the preparatory neural activity is essential during the preparatory period and the execution of the movement, whereas the most recent neural activity is essential during the release phase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The patterns of the attention weights suggested that the previous neural activity is essential for neural decoding during the preparatory period and execution of the movement, whereas the most recent neural activity is essential during the release phase. This finding is consistent with observations made in [ 5 , 36 , 37 , 38 ], where preparatory neural activity served as an initial condition for subsequent activity patterns. For the instructed delayed reach-to-grasp task, all findings from the three RNN-based neural decoders suggest that the preparatory neural activity is essential during the preparatory period and the execution of the movement, whereas the most recent neural activity is essential during the release phase.…”
Section: Discussionsupporting
confidence: 92%
“…Conventional neural decoding techniques process well-segmented neural activities in previous time windows where task-related information is likely encoded as spiking sequences. Thus, neural decoding may benefit from continuous neural activity because movement intention often occurs before execution [ 5 ]. Therefore, a sequence of spike count vectors from many preceding time windows is usually adopted to capture the neural response dynamics [ 6 ] and improve the decoding accuracy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach for latent trajectory modeling is to estimate the underlying linear dynamics of the latent state (Macke et al, 2011; Churchland et al, 2012; Pandarinath et al, 2018a). While the classical Kalman filter is the most thoroughly developed method for estimating the transition matrix in a linear dynamical system, a more appropriate generative model for neurons is the Poisson linear dynamical system (PLDS, Figure 3A) (Macke et al, 2011), which substitutes Poisson observations for the Gaussian emissions in the Kalman filter to directly model observed spike counts.…”
Section: Latent Factor Modelsmentioning
confidence: 99%
“…There exist many quantitative methods for relating population activity and computation (e.g., [22][23][24] ).…”
mentioning
confidence: 99%